Pengaruh Kebijakan Dividen, Total Assets Turnover (TATO), dan Laba Bersih Terhadap Harga Saham Perusahaan Sub Sektor Food and Beverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2020 - Beby Miraprilia; T. Alvi Syahri Mahzura; Sari Nuzullina Ramadhani (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
The purpose of this study was to determine the the effect of dividend policy (dividend payout ratio), total assets turnover (TATO), net income on stock prices in food and beverages sub-sector companies on the Indonesia Stock Exchange for the 2015-2020 period. The type of research used is causal associative. Samples were taken using purposive sampling method. The population used in this study are all food and beverages sub-sector companies, namely 33 companies with a sample of 7 food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The type of data used in this research is quantitative data. Sources of data used in this study is secondary data. The technique used by researchers to collect the data needed in this research is documentation. The data analysis technique used in this study is multiple linear analysis with the IBM SPSS version 25 technique. The results show that dividend policy (X1) has a positive and significant effect on stock prices, Total Assets Turnover (X2) has a positive and significant effect on stock prices. Stocks, Net Income (X3) has a positive and significant effect on the Stock Price.